Tourists’ threat appraisal, coping appraisal and protection intention in using food safety cues in the choice of Malaysian restaurants - Yasami, Mehri (2018)
Gaps exist in research on the ways in which international tourists can be motivated to use food safety cues in the choice of destination local restaurant in order to reduce the risk of contracting a foodborne illness. The primary purpose of the present study was to assess the utility of the Protection Motivation Theory (PMT) in predicting international tourists’ protection intentions concerning the threat of restaurant-associated foodborne illnesses in Malaysia. It employed a cross-sectional design with 431 Malaysia international first-time travelers as the respondents. The Covariance-Based Structural Equation Modeling was employed for data analysis. Before testing the actual hypotheses, confirmatory factor analysis was conducted to assess the reliability and construct validity of the measurement model. Path analysis indicated that the subcomponents of the coping appraisal, namely perceived selfefficacy and perceived response efficacy, positively and significantly predicted international tourists’ intentions to use food safety cues in the choice of Malaysian local restaurants. Among the threat appraisal subcomponents, the perceived vulnerability positively and significantly influenced protection intention while perceived severity did not predict protection intention. The positive significant influence of threat appraisal on coping appraisal was identified. Furthermore, coping appraisal fully mediated the relationship between threat appraisal and protection intention. The subjective norm only moderated the relationship between perceived vulnerability and protection intention. The outcomes of the comparative tests of hypothesis indicated that there were significant differences in international tourists’ protection intentions when they were classified by gender, trip plan, and nationality. Results of the study can be used to design communication resources developed to enhance international tourists’ intentions to use food safety cues in the choice of destination local restaurants. Educational and communication resources should emphasize self- efficacy, response efficacy, and vulnerability perception.